Description of a new species of Capederces (Coleoptera: Cerambycidae: Cerambycinae) from South Africa - Maquart, Pierre-Olivier; Noort, Simon Van (Zootaxa, 2017)
A new species of longhorned beetle in the tribe Tillomorphini, Capederces madibai sp. nov., is described from the “Albany district” in south-eastern South Africa. Adult specimens are illustrated and compared with the only other known species from this previously mono-specific genus: C. hauseri Adlbauer, 2001. An illustration of the female of C. hauseri is provided for the first time.